How to Build Innovation Capability in the RAC Industry to Face Industrial Revolution 4.0? - Asbari, Masduki; Asbari, Masduki; Wijayanti, Laksmi; Hyun, Choi C.; Purwanto, Agus; Santoso, Priyono Budi (International Journal of Psychosocial Rehabilitation, 2020)
Nowadays, innovations are much talked about, discussed, written and discussed in small to large classrooms, meeting rooms for managers and leaders. Innovation is associated with the need to survive amidst the industrial era 4.0. Innovation cannot be separated from personal knowledge and communal knowledge. Whereas knowledge consists of tacit and explicit knowledge both of which require good and continuous management. This study aims to measure the effect of tacit and explicit knowledge on innovation capability mediated by organizational learning. Data collection was carried out by simple random sampling via electronics in a population of Refrigeration and Air Conditioning (RAC) technicians in Indonesia. The results of the questionnaire returned were 632 and valid were 620 samples. Data processing using SEM method with SmartPLS 3.0 software. The results of this study are explicit and tacit knowledge has a positive and significant effect on innovation capability, both directly and through mediating organizational learning. This research novelty is proposing a model of building innovation capability in the RAC industry through tacit & explicit knowledge transfer with organizational learning as mediation. This research can open the way to increase readiness index in the RAC industry to deal with industrial revolution 4.0.